Predicting risk in the management of infection in orthopaedics - Dudareva, M (2023)
Bone and joint infections are a significant issue, affecting thousands more people each year and costing over £50 million to treat in the UK alone. Infection returns for many adults, even after intensive treatment with surgery and antibiotics. Ongoing bone and joint infection is painful and dispiriting; one in eight sufferers report a quality of life worse than death. People whose infection is not cured may need life-long antibiotics to suppress it, which can lead to antibiotic resistance and serious side-effects. Ongoing infection may require risky surgery, and itself has a higher mortality than many cancers.